TAX AVOIDANCE & CORPORATE RISK: AN EMPIRICAL STUDY IN MANUFACTURING COMPANY - Carolina, Verani; Oktavianti, Oktavianti; Handayani, Rini (Universitas Pendidikan Ganesha, 2019)
The purpose of this research is to test whether a company tax avoidance activity would affect the corporate risk. Tax avoidance measurement is done by applying cash effective tax rate formula, while the volatility rate of stock return formula is used to measure corporate risk. This research also testing the connection between cash effective tax rate and future tax rate volatility. This research shows that tax avoidance activity would impact both corporate risk and future tax rate volatility. Hopefully, the result of this research would help the decision makers such as the company?s managers who plans to do tax avoidance and the investors in making investment.